Results from shallow geophysical investigations in the northwestern sector of the island of Malta. (April 2017) - Pischiutta, M.; Villani, F.; D'Amico, S.; Vassallo, M.; Cara, F.; Di Naccio, D.; Farrugia, D.; Di Giulio, G.; Amoroso, S.; Cantore, L.; Mercuri, A.; Famiani, D.; et al.
Abstract: We performed geophysical investigations in the northwestern sector of the island of Malta to reconstruct velocity-depth models and provide shear-wave velocity profiles. We have chosen two sites, one located in Rabat (Malta) and another in the Golden Bay area. We used both active (seismic and electrical 2D-tomography, Multichanel Analysis of Surface Waves – MASW) and passive (2D arrays and single-station measurements using ambient noise) geophysical methods. Consistently with previous studies performed in this part of Malta, we have found that both sites are characterized by site resonance in the frequency range 1–2 Hz as an effect of the local lithostratigraphic succession that shows an impedance contrast at about 60–90 m depth. This resonance effect can have important implications on both seismic hazard as well as seismic risk evaluation of the region since the amplified frequency range coincides with the resonance frequencies typical of 5–10 storey buildings which are very diffuse in the Maltese Islands, especially after intense recent urbanization. We also highlight the importance of performing seismic velocity measurements even at rock sites. As an example, the Golden Bay site would be classified as class "A" following the EuroCode EC8 when considering only the outcropping lithology represented by limestone rocks. Conversely the subsoil characterization provided by this study has revealed that this site falls in the EC8 class "B", stressing the importance of direct geophysical measurements since the a-priori assignment to A-class could lead to wrong estimates in evaluating the site response. Highlights: We performed seismic and electrical geophysical investigations in Northern Malta. The reconstructed shear-wave velocity profile shows an impedance contrast. The impedance contrast causes a resonance peak between 1 and 2 Hz. This resonance effect can have important implications on the seismic hazard. We stress the importance of performing velocity measurements even at rock sites.